2006
DOI: 10.1089/mdr.2006.12.210
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Subtherapeutic Chlortetracycline on Antimicrobial Resistance in the Fecal Flora of Swine

Abstract: The aims of this research were to determine the association between inclusion of subtherapeutic chlortetracycline in the diets of swine and the prevalence and antimicrobial resistance of Salmonella; define the association between inclusion of subtherapeutic chlortetracycline and antimicrobial resistance in the aerobic Gram-negative fecal flora of swine; and estimate the proportion of total model variance attributable to farm, pig, and colony level effects. There was no association between subtherapeutic chlort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 45 publications
2
21
0
Order By: Relevance
“…For instance, they found an increased frequency of the following genes associated with feeding of ASP250: the aph(3″)-Ib,aph(6′)-Ic gene conferring resistance to streptomycin, the ImrA gene related to lincomycin resistance; the emrD, mdfA, mdtH, bcr multi-drug resistance efflux pump genes conferring resistance to chloramphenicol, tetracycline, deoxycholate, fosfomycin, florfenicol, and sulfathiazole; and the acrAmulti-drug resistance efflux pump gene responsible for resistance to many antimicrobial classes including phenicols, aminoglycosides, macrolides, and β-lactams (Looft et al, 2012). Funk et al (2006), in a phenotypic resistance study, also found that inclusion of chlortetracycline in the pig diet has an effect on resistance to multiple antimicrobials, including ampicillin, ceftriaxone and tetracycline, in the gram negative fecal flora of swine (Funk et al, 2006). Interestingly, in our study, whereas prevalence of resistance to antimicrobials in the same classes as the medicated feed, such as tetracycline and ampicillin, increased and remained high throughout the study, during which time pigs continued to be medicated, prevalence of resistance to antimicrobials of other classes, such as streptomycin, trimethoprim-sulfamethoxazole and sulfisoxazole, initially increased and then decreased with time.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, they found an increased frequency of the following genes associated with feeding of ASP250: the aph(3″)-Ib,aph(6′)-Ic gene conferring resistance to streptomycin, the ImrA gene related to lincomycin resistance; the emrD, mdfA, mdtH, bcr multi-drug resistance efflux pump genes conferring resistance to chloramphenicol, tetracycline, deoxycholate, fosfomycin, florfenicol, and sulfathiazole; and the acrAmulti-drug resistance efflux pump gene responsible for resistance to many antimicrobial classes including phenicols, aminoglycosides, macrolides, and β-lactams (Looft et al, 2012). Funk et al (2006), in a phenotypic resistance study, also found that inclusion of chlortetracycline in the pig diet has an effect on resistance to multiple antimicrobials, including ampicillin, ceftriaxone and tetracycline, in the gram negative fecal flora of swine (Funk et al, 2006). Interestingly, in our study, whereas prevalence of resistance to antimicrobials in the same classes as the medicated feed, such as tetracycline and ampicillin, increased and remained high throughout the study, during which time pigs continued to be medicated, prevalence of resistance to antimicrobials of other classes, such as streptomycin, trimethoprim-sulfamethoxazole and sulfisoxazole, initially increased and then decreased with time.…”
Section: Discussionmentioning
confidence: 99%
“…Tenfold serial dilutions of the filtrate were prepared, and 100-l samples of the dilutions were spread on MacConkey plates (AEB 151602; AES, Ker Lann, France) containing 0 and 16 g/ml of ampicillin. MacConkey agar is classically used for selective growth of Enterobacteriaceae (7,8,11,30). Enterobacteriaceae growing in the presence of 16 g/ml of ampicillin were classified as resistant.…”
Section: Methodsmentioning
confidence: 99%
“…However, due to a variety of potential confounding factors related to the intestinal microbial ecology in the host (i.e., the pigs), the susceptibility/resistance characteristics of the Salmonella strain present (or introduced) in the herd, and also to the dose and route of administration of the drugs, reported results are usually inconsistent, particularly when trying to determine the potential role of specific antibiotics as risk factor for Salmonella (Beloeil et al, 2007;Farzan et al, 2006;Funk et al, 2007;Funk, LeJeune, Wittum, & Rajala-Schultz, 2006;Hotes et al, 2010;Leontides et al, 2003;Rajic, Chow, et al, 2007;van der Wolf et al, 2001). On-farm antibiotic use is only one factor affecting bacterial resistance, which is also affected by several other on-farm factors that also influence the emergence of resistant foodborne pathogens, such as Salmonella (Farzan, Friendship, Dewey, Poppe, & Funk, 2010;Varga, Rajic, McFall, Reid-Smith, & McEwen, 2009).…”
Section: On-farm Risk Factorsmentioning
confidence: 99%